Znaczenie diagnostyki i leczenia trombolitycznego w udarze nieokrwiennym mózgu = The importance of diagnosis and treatment thrombolytic in ischemic stroke - Siminska, Joanna; Pietkun, Katarzyna; Siedlecki, Zygmunt; Grzyb, Sebastian; Nowacka, Krystyna; Hagner, Wojciech; Grobelska, Kinga; Beuth, Wojciech (Journal of Education, Health and Sport, 2016)
Siminska Joanna, Pietkun Katarzyna, Siedlecki Zygmunt, Grzyb Sebastian, Nowacka Krystyna, Hagner Wojciech, Grobelska Kinga, Beuth Wojciech. Znaczenie diagnostyki i leczenia trombolitycznego w udarze nieokrwiennym mózgu = The importance of diagnosis and treatment thrombolytic in ischemic stroke. Journal of Education, Health and Sport. 2016;6(8):363-374. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.60602 http://ojs.ukw.edu.pl/index.php/johs/article/view/3766 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.08.2016. Revised 08.08.2016. Accepted: 19.08.2016. ZNACZENIE DIAGNOSTYKI I LECZENIA TROMBOLITYCZNEGO W UDARZE NIEOKRWIENNYM MÓZGU THE IMPORTANCE OF DIAGNOSIS AND TREATMENT THROMBOLYTIC IN ISCHEMIC STROKE Siminska Joanna1, Pietkun Katarzyna1,2, Siedlecki Zygmunt3, Grzyb Sebastian3, Nowacka Krystyna1,6, Hagner Wojciech1,6, Grobelska Kinga4, Beuth Wojciech5,6 1 Katedra i Klinika Rehabilitacji Collegium Medicum w Bydgoszczy 2 Katedra Kosmetologii i Dermatologii Estetycznej Collegium Medicum w Bydgoszczy 3 Klinika Neurochirurgii i Neurotraumatologii i Neurochirurgii Dziecięcej Collegium Medicum w Bydgoszczy 4 Klinika Medycyny Ratunkowej Collegium Medicum w Bydgoszczy 5 Wojewódzki Szpital Specjalistyczny we Włocławku 6 Kujawska Szkoła Wyższa we Włocławku Streszczenie W pracy przedstawiono aktualne zasady postępowania przedszpitalnego podejmowanego przez zespół ratownictwa medycznego i postępowania wczesnoszpitalnego, które ma wpływ na dalszy proces leczenia. Przedstawiono również zastosowanie leczenia trombolityczego w tzw. Złotej godzinie udarowej. Należy mieć na uwadze, że każde minuty, które odraczają podjęcie właściwego leczenia udaru niedokrwiennego mózgu przyczyniają się do uniemożliwienia wdrożenia nowoczesnych, specyficznych metod leczenia ( leczenie trombolityczego). Słowa kluczowe: badania diagnostyczne, postępowanie ratunkowe, udar mózgu. Summary The paper presents the current rules of conduct undertaken by a team of prehospital emergency medical services and conduct prehospital, which has an impact on the further process of treatment. It also presents the use of the treatment thrombolysis. Golden time of impact. It should be noted that every minute that defer taking the proper treatment of ischemic stroke contribute to preventing the implementation of modern, specific treatment (treatment thrombolysis.) Key words: diagnostic tests, emergency procedures, stroke.